The impact of age on comparative diagnostic accuracy of temporal artery thermometers and non-contact infrared thermometers for fever detection: a systematic review and meta-analysis - Kwo-Chen Lee; Yun-Ping Lin; Ya-Ling Tzeng; Wen-Chun Liao; Chyi Lo; Pei-Yun Chen; Shu-Hua Lu (BMC Infectious Diseases)
Abstract Background Non-invasive temporal artery thermometers (TATs) and non-contact infrared thermometers (NCITs) are increasingly used in community settings to measure body temperature. Existing research predominantly focuses on pediatric populations, yet the accuracy and precision of TATs and NCITs for fever screening across age groups remain unclear. This study aims to assess age-related differences in the diagnostic accuracy of TATs and NCITs for fever detection. Methods A systematic review and meta-analysis were conducted, sourcing data from PubMed, MEDLINE, CINAHL, EMBASE, Cochrane Library, ProQuest, and Web of Science. Prospective studies comparing TATs and NCITs against body temperature measurement methods were included. Two independent researchers extracted data, and study quality was assessed with the QUADAS-2 tool. Pooled estimates of sensitivity, specificity, and the hierarchical summary area under the receiver operating characteristic (ROC) curves were calculated using STATA version 17. Results This meta-analysis included 34 studies with 28,996 participants, of whom 5,358 were febrile. For TATs, 22 studies with 9,894 readings yielded a pooled sensitivity of 0.59 (95% CI: 0.40–0.76) and specificity of 0.91 (95% CI: 0.83–0.96). Sensitivity was higher at fever thresholds > 38 °C (0.71, 95% CI: 0.60–0.80), and higher in children (0.77, 95% CI: 0.66–0.85) than in adults (0.48, 95% CI: 0.30–0.67). Similar sensitivities were observed between rectal and other standards (0.70, 95% CI: 0.59–0.80 vs. 0.70, 95% CI: 0.41–0.89). For NCITs, 16 studies with 14,234 readings yielded a pooled sensitivity of 0.70 (95% CI: 0.54–0.82) and specificity of 0.94 (95% CI: 0.90–0.97). Sensitivity improved at fever thresholds > 38 °C (from 0.70 to 0.75, 95% CI: 0.55–0.88) and was higher in children compared to the overall estimate (0.79 vs. 0.70, 95% CI: 0.62–0.90). Comparable sensitivities were noted between axillary and other standards (0.73, 95% CI: 0.30–0.94 vs. 0.75, 95% CI: 0.49–0.90). Conclusions TATs and NCITs show variable diagnostic accuracy across age groups, with higher sensitivity in children and at elevated fever thresholds. This variability underscores the importance of age-specific use of these thermometers and highlights the need for further research to optimize diagnostic performance across populations.